The 5 X 200 m step test lactate curve model: Gender specific characteristics in elite Greek senior freestyle swimmers - Thanopoulos, V. (Serbian Journal of Sports Sciences, 2010)
The study aimed to define the differences in the characteristics of the lactate curve in elite Greek freestyle swimmers with respect to gender. It included 27 swimmers (14 men and 13 women), all members of the senior Greek swimming national team. All swimmers were tested by a standardized method of a 5 x 200 m step test in the period between 2004 and 2007. Besides the dependence equation showing the relationship swim velocity - lactate concentration, the lactate curve model was defined by 10 other variables. The results revealed a statistically significant general gender-specific difference in the observed measurement space, at Wilks` Lambda Value 0.366, F=2.770, p=0.034. A partial difference was determined in 6 variables: swim velocity at the concentrations of 2, 4, 8 mmol•L-1 at the individual anaerobic threshold, at LaTestPeak and Index LaIndAnT / LaTestPeak. The defined lactate curve models had the following characteristics: y = 0.00243e5.26297X in women swimmers, where the model explained 94.65 % of the variability (R2 = 0.9465) with a prediction error of 5.35 %; y = 0.00121e5.53729X in men swimmers, where the model explained 98.07 % of the variability of the dependence analyzed (R2 = 0.9807) with a prediction error as low as 1.93 %.